Microstructure and interface characteristics of B4C, SiC and Al2O3 reinforced Al matrix composites: a comparative study - Shorowordi, Kazi Md; Laoui, Tahar; Haseeb, A.S. Md. Abdul; Celis, Jean Pierre; Froyen, Ludo (Elsevier, 2003)
Three aluminium metal matrix composites containing reinforcing particles of B4C, SiC and Al2O3 (0-20 vol.) were processed. The stir-casting manufacturing route followed by hot extrusion was utilized, being one of the cost-effective industrial methods. A clear interfacial reaction product/layer was found at Al-SiC interface for composites held for a relatively long processing time (>30 min). No reaction product was observed at Al-B4C and Al-Al2O3 interfaces at the resolution limit of the SEM used. On the other hand, two secondary phases (alumina and another phase containing aluminium, boron and carbon) were found in the aluminum matrix away from the interface in Al-B4C composites. From the fracture surface analysis, B4C reinforced At composite seemed to exhibit a better interfacial bonding compared to the other two composites. (C) 2003 Elsevier B.V. All rights reserved.